2019
DOI: 10.3390/electronics8121466
|View full text |Cite
|
Sign up to set email alerts
|

Brain Computer Interface-Based Action Observation Game Enhances Mu Suppression in Patients with Stroke

Abstract: Action observation (AO), based on the mirror neuron theory, is a promising strategy to promote motor cortical activation in neurorehabilitation. Brain computer interface (BCI) can detect a user’s intention and provide them with brain state-dependent feedback to assist with patient rehabilitation. We investigated the effects of a combined BCI-AO game on power of mu band attenuation in stroke patients. Nineteen patients with subacute stroke were recruited. A BCI-AO game provided real-time feedback to participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…In a previous study, Lim and Ku introduced a new paradigm combining a BCI game and an AO [16]. This BCI-AO paradigm induced greater mu suppression than AO alone in healthy subjects and patients with stroke [16,17]. In line with previous work, the present study revealed that the BCI-AO + PES paradigm could significantly induce corticospinal plasticity compared to AO + PES or AO alone in both healthy and stroke groups.…”
Section: Bci-ao + Pes Induced Increase In Corticospinal Excitabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…In a previous study, Lim and Ku introduced a new paradigm combining a BCI game and an AO [16]. This BCI-AO paradigm induced greater mu suppression than AO alone in healthy subjects and patients with stroke [16,17]. In line with previous work, the present study revealed that the BCI-AO + PES paradigm could significantly induce corticospinal plasticity compared to AO + PES or AO alone in both healthy and stroke groups.…”
Section: Bci-ao + Pes Induced Increase In Corticospinal Excitabilitysupporting
confidence: 88%
“…In the BCI-AO paradigm, attentive watching could be superiorly and robustly detected by steadystate visual evoked potential (SSVEP) evoked exogenously by the flickering action video compared to other methods utilizing endogenous factors of electroencephalogram (EEG) such as alpha and beta band amplitude of EEG. Proper feedback according to the state of patient engagement could induce stronger mu suppression than a paradigm simply showing an action video in healthy volunteers as well as in patients with stroke has been previously demonstrated [16,17]. The BCI-AO paradigm adopted the flickering action video scheme that could achieve robust detection and MNS activation at the same time, providing timely feedback and eliciting a stronger MNS.…”
Section: Introductionmentioning
confidence: 99%
“…All channels were used to generate the real-time topography of the brain dynamic potential for surveillance. Alpha suppression reflects an event-related desynchronization (ERD) of the EEG caused by an increase in neural activity [ 26 ], which has been widely utilized in BCI training field and has promising outcome [ 27 , 28 ]. To compute suppression, the C3 or C4 channel was chosen according to the subject’s lesion side.…”
Section: Methodsmentioning
confidence: 99%
“…Shu et al (2017Shu et al ( , 2018 and Ren et al (2020) improved the SMR-BCI performance via proprioceptive stimulation before the motor imagery (MI) task. Choi et al (2019), Nagai andTanaka (2019), andFujiwara et al (2021) found users' ERD/ERS was enhanced when they performed MI task with motor observation. It is recognized that enhanced ERD/ERS of stroke patients, meaning enhanced motor-related cortical activation (Pfurtscheller and Lopes da Silva, 1999;Pfurtscheller et al, 2006b), can improve users' engagement and decoding accuracy for BCI system, which could help maximize brain plasticity and restore motor and cognitive function for stroke patients (Bundy et al, 2017;Nagai and Tanaka, 2019).…”
Section: Introductionmentioning
confidence: 99%